Examining the Relationship between Perpetual Peace and Military Sociology - Sedat Doğan (İstanbul Üniversitesi Sosyoloji Dergisi)
Immanuel Kant’s political writings, which represent a philosophical revolution in the name of the modern world, have always remained important. Kant’s Perpetual Peace is one of these writings. The agenda of perpetual peace, which became evident in the early eighteenth century, was still on the agenda at the end of the century, as is evident from this text of Kant. The reason for this is that the dynamo of the Westphalian order established after the Thirty Years’ War was the wars that prevailed in Europe. Almost every thinker of the period seems to have pondered on war and peace. However, especially in terms of sociology, which was established and institutionalized in the nineteenth century, war have become a more permanent agenda than peace. The function of sociology in describing social reality and solving identified problems made an unrealized peace as a part of social reality an accidental issue. Due to the autonomy of the discipline and the accidental position of peace, sociological knowledge of the soldier, army and war has become alienated from the philosophical theory of war and peace over time. The institutionalization of contemporary military sociology in the conditions of the Second World War made even the accumulation in classical sociology secondary. Contrary to these developments, the present article is based on the assumption that there are deep-rooted links between the philosophical theory of peace and sociological explanation of war. The aim of the article, as an example of this connection, is to show that the factual determinations on which the normative proposals in Kant’s aforementioned text are based can be examined from the perspective of military sociology.